Flexible Pavement Distress Analysis Using the Pavement Condition Index (PCI) Method - Rajak, Irsandi A; Altarans , Indra; Faruk, Fitriyanti (PT. Sangadji Media Publishing, 2025)
Road infrastructure along the Kalaodi–Fabaharu corridor in Tidore Kepulauan has exhibited varying levels of surface deterioration, highlighting the need for an objective and standardized evaluation to determine appropriate treatment priorities. This study aims to assess the condition of flexible pavement using the Pavement Condition Index (PCI) method while also identifying key factors contributing to the observed damage. Field surveys were conducted on twenty selected road segments to record distress types, severity levels, and the extent of deterioration in accordance with ASTM D6433-11 guidelines. These data were then used to calculate PCI values, enabling the classification of pavement conditions across the study area. The findings show that PCI values range from 15 to 56, with an overall average of 27.48, indicating that the general pavement condition falls within the